Cardinal Bea’s Council - Madrigal, SJ, Santiago (Razón y fe, 2018)
This article presents the internal development of the Second Vatican Council, as well as the elaboration of some of its most significant documents by one of its most emblematic personalities, Agustín Bea, a Cardinal devoted to ecumenism and unity. For this purpose, the author has picked up a series of articles by the notable Jesuit that were published in Razón y Fe on the occasion of the ecumenical council.
Keywords: Cardinal Bea; Cardinal Ottaviani; Razón y Fe; Christian unity; freedom of religion; non-Christian religions